THE CLIMATE IMPACT TOWARDS FORM, MATERIALS, AND CONSTRUCTION OF PAPUA VERNACULAR HOUSES - Pricillia Soedhijanto; Georgeanne Elaine; Angelique Hillary; Leonard Amadeo; Agus Dwi Hariyanto (Universitas Indraprasta PGRI, 2023)
Climate is an important aspect in architectural design, including residential buildings. The climate will have a direct effect on the comfort of living for its inhabitants. Indonesia is a country with various tribes and cultures. The tribes are spread over various islands with very diverse local climatic conditions. Local communities have long ago designed their homes as a strategy to deal with climatic conditions, and the local Papuan people are no exception. Weather conditions in Papua which are quite extreme finally force residents to always adapt to their natural surroundings. The Dani, Asmat and Mee tribes are tribes living in Papua with contrasting climatic elements. The dwellings of these tribes: the Honai house, the Jew house, and the Yame Owaa house each have different shapes, materials and construction. The research aims to find the relationship between climatic elements and the shape, material, and construction of Papuan vernacular houses. The researcher conducted a literature review which was then analyzed using a qualitative approach. The results showed that each difference in form, material, and construction was also influenced by different climatic elements. Form, material, and construction also influence each other in dealing with local climatic conditions. Seeing the minimal number of traditional Papuan houses that are still standing, it is hoped that this research will be able to support and support research on the Papua region and its surroundings in the future. In addition, with an understanding and utilization of forms, materials and construction, the preservation of traditional Papuan houses can be maintained.